EMPOWERMENT OF MEDICAL RECORD OFFICERS IN INCREASING OUTCOME PATIENT SATISFACTION EFFORTS IN HOSPITALS GRANDMED LUBUK PAKAM - Felix Kasim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Medical record as a form of documentation of health services and a form of patient administrative responsibility and patient reference. The quality of medical records describes an implementation of the quality of health services such as health centers, clinics and hospitals. The purpose of this activity is to socialize and assist medical record officers in increasing outpatient satisfaction at Grandmed Hospital. The implementation of this community service activity began with collecting data on the number of officers in the outpatient medical record unit at Grandmed Lubuk Pakam Hospital. Then the team made direct observations in the RM unit and saw the activities of officers while providing services to patients at the hospital. Furthermore, outpatients were given a questionnaire regarding the satisfaction of medical record services. Furthermore, socialization, education and mentoring training were carried out through lectures and discussions about health services according to standard operating procedures (SOPs). After socialization, outpatients were given a questionnaire again to assess the improvement of medical record services. Based on the results of the socialization activity, the respondent's score before socialization and education was 7 and the lowest value was 4. Meanwhile, the respondent's value after being given socialization and education to the respondent increased by 10, the lowest score was 6 and the average respondent's score was 9.8. . Based on the results of the activity, it was found that 20 outpatients at Grandmed Hospital showed that the level of service satisfaction was 93% while dissatisfied was 3%. Based on this socialization activity, it was concluded that the medical record service unit officers experienced an increase in knowledge and the results of the evaluation of services for outpatients, namely patients were satisfied with medical record services, which was 93%.